Bahasa Inggris KORELASI ANTARA PEMODELAN INVERSI 3-D MAGNETOTELLURIK DENGAN DATA SUMUR DI LAPANGAN PANAS BUMI PATUHA: CORRELATION BETWEEN 3-D MAGNETOTELLURIC INVERSION MODEL WITH DRILLING DATA IN PATUHA GEOTHERMAL FIELD - Chevy Iskandar; Yunus Daud (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
The Patuha geothermal field is located in West Java Province, Indonesia and developed by state owned company PT Geo Dipa Energi (Persero). The Commercial Operation Date (COD) for Patuha was in September 2014 with plant capacity of 1x60 MW. Until now, Patuha Unit I geothermal field has been running for almost 7 years. The current production wells have experienced a natural decline, which is showed by a reduction in production capacity to the initial production. This causes the steam supply to the Power Plant Unit I to be not optimal, so a make-up well program is needed. Furthermore, to support the addition of electricity production capacity from geothermal energy in Indonesia, the development of the Patuha Geothermal Field is planned to be carried out for the next Power Plant Unit’s expansion (Unit 2 and Unit 3). Nevertheless, determining the location for both make-up and development drilling might still pose high risks. This is especially because the development area (where production and injection wells are located) is only concentrated in the eastern area of the contract area. Geophysical data especially Magnetotelluric (MT) has an indispensable role considering the limited data and the limited number of existing wells that cover the entire Patuha prospect area. To understanding the subsurface feature and see the correlation between MT model with well results in Patuha Geothermal Field, MT and TDEM survey were conducted in the eastern and western parts of Patuha area with total 100 stations. Considering the complexity of the subsurface condition in volcanic area, 3-D inversion of the MT data will be the most representative approach to investigate geothermal system in Patuha Geothermal Field. An obvious subsurface resistivity distribution revealed by the 3-D inversion showed a good agreement with well results especially in mapping the temperature distribution both vertically and horizontally. Generally, the resistivity distribution consists of a conductive zone (1–10 ohm-m) at the shallow part overlying a reservoir zone with a rather higher resistivity range (20–60 ohm-m). The conductive zone (<10 ohm-m) is correlated with Base of Conductor (BOC) of the wells that indicated by the presence of the argillic mineral. Meanwhile, the resistivity value around 15-20 ohm-m is correlated with Top of Reservoir of the production or injection well which is characterized by the presence of a convective temperature. In addition, from the results of resistivity mapping there is a very good correlation also in determining of reservoir boundary which is characterized by the presence of reverse temperature from the well. These results can be used as a guidance for better development strategy and drilling prognosis for the next drilling campaign especially in the area which limited number of wells.